IMPLEMENTASI NILAI-NILAI ETIKA DALAM PEMBELAJARAN SAINS UNTUK MEMBANGUN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK - Gresinta , Efri; Rahmawati, Rahmawati; Suharyati, Henny (Journal of Industrial Engineering & Management Research, 2023)
Critical thinking can be interpreted as the processes and abilities used to understand concepts, apply, synthesize and disseminate the acquired or generated information. Not all information obtained can be used as knowledge that is believed to be true to be used as a guide in action, and not always the information produced is true information. Critical thinking is a higher-order thinking skill and has been instrumental in moral development, social development, mental development, cognitive development, and scientific development. The implementation of ethical values in science learning is an alternative strategic solution to overcome moral degradation in society and in the educational environment. The type of research used is literature research or literature study where researchers rely on various literature to obtain research data and use a qualitative approach because the data produced is in the form of words or descriptions. The purpose of this study is to know ethical values and critical thinking skills in students. This study discusses how the implementation of ethical values in science learning to build critical thinking skills for students.